The Role of Sustainability Disclosure in Shaping the Performance of State-Owned Enterprises: An Indonesian Perspective - Sanda Patrisia Komalasari; Khalilul Rahman; Andesta Brilian Nelson (Universitas Negeri Padang, 2026)
Despite the growing emphasis on sustainable development, the extent to which sustainability transparency influences the performance of state-owned entities remains empirically debated. This study investigates the impact of sustainability disclosure on the corporate performance—conceptually defined as